Information theory and optimization techniques in scientific research : interdisciplinary approach - Prakash, Om (Deutscland : VDM, 2010)
This book presents state of the art in Mathematics, Statistics, Operational Research, Information Theory, Coding Theory, Reliability, Ecology, Bibliometry, Inventory, Mathematical models, Mathematical sciences and Optimization techniques by distinguished researchers. It covers various topics and current problems of interest in different disciplines of Mathematical and Biological Sciences. The book will serve as source of ready reference for the scientific community.
Index 236-239p.
Keywords: Cyclic codes; Inventroy modeling; Operational Research